Značilnosti razvoja in delovanja Centralne tehniške knjižnice Univerze v Ljubljani (1949–1991) - Čučnik-Majcen, Nada (Knjižnica, 2020)
The article describes the activities and development of the Central Technical Library at the University of Ljubljana during the time between its foundation and 1991. The library was established in 1949 at the initiative of university teachers and researchers and with the great support of the political leadership of the country at that time; in all those years, it functioned significantly different from other academic and special libraries. Despite its function as a university library, through its innovative approach and indepth international contacts, the library effectively served a wider purpose, i.e. as information and library support for the economy of the country and as a driving force for special libraries. The innovative approach of CTK’s operation in that period was mainly reflected in the fact that the user with his information needs was put into the focus of the library’s operation. An example of such a userfriendly service was home borrowing of individual issues of periodicals, which was not a common practice of other libraries. From the perspective of involvement in international professional networks, the role of the CTK in the professional association IATUL was of special importance. Today, after major social and technological changes, the CTK is a modern university library, which has retained its characteristic innovation and involvement in international cooperation. Innovation in the CTK today is reflected primarily in the important role of the library in facilitating an open national research and educational infrastructure; and international cooperation is primarily reflected in the active role of the CTK in professional organizations and forums such as LIBER, European Open Science Cloud or Coalition S.
Keywords: 1949/1991; Centralna tehniška knjižnica Univerze v Ljubljani; knjižnični informacijski sistemi; Ljubljana; specialne knjižnice; visokošolske knjižnice